Sliding Mode Variable Structure Vector Control of Permanent Magnet Synchronous Machine Servo System for Side Scan Sonar (Xibei Gongye Daxue Xuebao, 2018)
To control the distance between the side scan sonar and the seabed, a permanent magnet synchronous machine(PMSM) servo system is designed, and the overall structure of the system and the design scheme of each part are presented. The maximum torque per ampere (MTPA) vector control method is adopted to enhance the power factor and dynamic performances of the system, and based on MTPA vector control method, according to the harmful effects of the dynamic load in the servo control of sonar, the sliding mode variable structure (SMVS) vector control method is proposed, and the robustness of the servo system is effectively improved. The mechanism of the MTPA and SMVS vector control method is demonstrated in detail, and their effectiveness is verified.